Marketing Plan for Small Luxury Hotel - Davydova, Maria (2018)
This master's thesis is aimed at developing marketing strategies for the launching of a new boutique hotel on the Prague market. The work consists of theoretical and practical parts. Theory is based on marketing learnings and theories with a bias towards the luxury segment mostly. The practical part is based on the analysis of tourism in the Czech Republic as a whole, the attractiveness of Czech market for tourists, tourists’ inflows and changes of it during past 5 years. The evaluation of competition in the tourist accommodation market in the Czechs and Prague is also covered as well as the evaluation of direct competitors and their characteristics. The practical part also includes a qualitative analysis to identify and determine the nuances that help in developing a marketing mix. Qualitative analysis is conducted in the form of personal interviews with the representatives of the target audience. The results of the research are presented in the form of recommendations for the development of promotion types. . Promotion strategies also include collaboration with a Czech designer to attract the audience and add value. It involves also product descriptions, which are presented by description of the boutique hotel in particular and the process of service, which implements direct communication with a customer.